2014
DOI: 10.1155/2014/203518
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Dihydropyridine Calcium Channel Blockers: Homology Modeling of the Receptor and Assessment of Structure Activity Relationship

Abstract: 1,4-Dihydropyridine (DHP), an important class of calcium antagonist, inhibits the influx of extracellular Ca+2through L-type voltage-dependent calcium channels. Three-dimensional (3D) structure of calcium channel as a receptor for 1,4-dihydropyridine is a step in understanding its mode of action. Protein structure prediction and modeling tools are becoming integral parts of the standard toolkit in biological and biomedical research. So, homology modeling (HM) of calcium channel alpha-1C subunit as DHP receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Voltage-gated calcium channels play an important role in the entry of Ca 2+ ions into excitable cells and are also involved in a series of calcium-dependent processes, such as muscle contraction, hormone or neurotransmitter release, gene expression, and cell death (Augustine et al 1987;Miller 1987). Voltage-gated calcium channels are blocked by 1,4-d i h y d r o p y r i d i n e s ( D H P s ) s u c h a s n i f e d i p i n e , phenylalkylamines such as verapamil, and benzothiazepines such as diltiazem (Shaldam et al 2014). They are multisubunit complexes, comprising alpha-1, alpha-2, beta, and delta subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Voltage-gated calcium channels play an important role in the entry of Ca 2+ ions into excitable cells and are also involved in a series of calcium-dependent processes, such as muscle contraction, hormone or neurotransmitter release, gene expression, and cell death (Augustine et al 1987;Miller 1987). Voltage-gated calcium channels are blocked by 1,4-d i h y d r o p y r i d i n e s ( D H P s ) s u c h a s n i f e d i p i n e , phenylalkylamines such as verapamil, and benzothiazepines such as diltiazem (Shaldam et al 2014). They are multisubunit complexes, comprising alpha-1, alpha-2, beta, and delta subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Atoms N1 and C4 of the 1,4-DHP ring can be marginally displaced from the mean plane of the boat (Linden et al, 2002). An aryl group in the 4-position of the 1,4-DHP ring is essential for optimal activity (Shaldam et al, 2014). One study showed that an aryl ring with halogen or other electron-withdrawing groups exhibits higher receptorbinding activity (Takahashi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This again implies the importance of the ring lipophilicity in the calcium antagonist activity of DHPs. 33) Ester groups at 3-and 5-positions are simply methyl ester groups in both nifedipine and the two compounds 3a and g. The down methyl ester group stabilizes the lipophilic bracelet while the other methyl ester group is projected in the water lake core of the receptor and participates in chelating the Ca 2+ cofactor (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…This compound has benzyl ester substituent with total ten carbon atom side chain (five extended carbon atom at 3-and 5-positions). This bulky side chain may interfere with the affinity axis (Tyr 1149 and Tyr 1460 ) binding 33) which may result in abolishing ring to ring hydrophobic attraction force between the chlorophenyl ring and Tyr 1460 . The down benzyl ester group phenyl ring makes the affinity axis instead of important stabilization of the hydrophobic bracelet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation